PROTECTIVE ROLE AND ANTIOXIDANT ACTIVITY OF AQUEOUS EXTRACT OF ROSMARINUS OFFICINALIS AGAINST TRICHLOROACETATE-INDUCED TOXICITY IN LIVER OF MALE RATS - Abozid, Medhat Mostafa; Farid, Hoda Ea (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The current study was designed to estimate the potential protective role of the aqueous extract of rosemary (AER) (Rosmarinus officinalis) against trichloroacetic acid (TCA)-created hepatotoxicity in male albino rats. Methods: Forty male albino rats were separated into four groups of ten: Group I served as control; Group II was given AER (200 mg/kg/day) by gavage; Group III received TCA at the dose 50 mg/kg/day, and Group V was treated with AER (200 mg/kg/day) and received TCA (50 mg/kg/day). The experiment was carried out for 2 months. Results: The toxicity of TCA for rats was revealed by an elevation in liver marker enzymes activities (gamma-glutamyl transferase [GGT], alkaline phosphatase [ALP], aspartate transaminase [AST], alanine aminotransferase [ALT]) and conjugated bilirubin (CB) level, and a decrease in albumin and total protein (TP) levels. The TCA administration also caused a significant increase in the activities of catalase (CAT), glutathione peroxidase (GPx) and superoxide dismutase (SOD), and also malondialdehyde (MDA) level in liver tissues. These biochemical effects were accompanied by histological indicators of liver damage. Treatment with ARE recovered the liver damage instigated by TCA, as showed by perfection of liver enzyme markers (GGT, ALT, AST, ALP), CB, TP and albumin; as well as antioxidant parameters (CAT, SOD, GPx) and lipid peroxidation (MDA) and amelioration of histopathology changes in the liver tissues. Conclusion: It could be concluded that AER supplementation for 2 months in TCA-induced toxicity in rats benefited hepatic antioxidant status and improved liver injury and damage in male albino rats exposed to TCA.